2011
DOI: 10.1117/1.3524304
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of ceroid formation in atherosclerotic plaque: in situ studies using a combination of Raman and fluorescence spectroscopy

Abstract: Abstract. Accumulation of the lipid-protein complex ceroid is a characteristic of atherosclerotic plaque. The mechanism of ceroid formation has been extensively studied, because the complex is postulated to contribute to plaque irreversibility. Despite intensive research, ceroid deposits are defined through their fluorescence and histochemical staining properties, while their composition remains unknown. Using Raman and fluorescence spectral microscopy, we examine the composition of ceroid in situ in aorta and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 38 publications
(45 reference statements)
2
32
0
Order By: Relevance
“…Based on the findings of this study and information gleaned from the literature (21,22), various hypotheses can be made about the potential sources of NIRAF in atherosclerotic plaques and its potential relationship to coronary wall inflammation. NIRAF in atherosclerotic plaque may arise from the modification of lipids and lipoproteins by oxidative stress (21,22).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Based on the findings of this study and information gleaned from the literature (21,22), various hypotheses can be made about the potential sources of NIRAF in atherosclerotic plaques and its potential relationship to coronary wall inflammation. NIRAF in atherosclerotic plaque may arise from the modification of lipids and lipoproteins by oxidative stress (21,22).…”
Section: Discussionmentioning
confidence: 98%
“…Based on the findings of this study and information gleaned from the literature (21,22), various hypotheses can be made about the potential sources of NIRAF in atherosclerotic plaques and its potential relationship to coronary wall inflammation. NIRAF in atherosclerotic plaque may arise from the modification of lipids and lipoproteins by oxidative stress (21,22). Studies have shown that ceroid, a protein-lipid oxidation byproduct found in atherosclerotic plaque, has a yellow fluorescence spectrum (22) and it is possible that the tail of ceroid's fluorescence emission may extend into the NIR.…”
Section: Discussionmentioning
confidence: 98%
“…Sudanophilic ceroids could be also stained by Oil Red O on deparaffinised sections, providing evidence of lipid entrapment in insoluble bodies. Ceroids can colocalize with iron deposits within cells and tissue [49] and the presence of Fenton-dependent and myeloperoxidasedependent LDL peroxidation products, free cholesterol and cholesteryl esthers, haemoglobin and collagen has been recently identified in ceroids by Raman and fluorescence spectroscopy [50] suggesting that the different components of RBC are involved in ceroid genesis. Ceroids can remain present within the tissue, even when other RBC signatures have partly or completely disappeared.…”
Section: Tissue Markers Of Iphmentioning
confidence: 97%
“…3,4 Furthermore, studies have shown that atherosclerosis is associated with higher concentrations of modified LDL (moLDL) in the bloodstream. 5,6 Recently, Haka et al 7 used a combination of Raman and fluorescence spectroscopies to investigate the atherosclerotic plaque formation.…”
Section: Introductionmentioning
confidence: 99%